TAT‐dextran–mediated mitochondrial transfer enhances recovery from models of reperfusion injury in cultured cardiomyocytes. Issue 9 (25th March 2020) - Maeda, Hideki; Kami, Daisuke; Maeda, Ryotaro; Murata, Yuki; Jo, Jun‐ichiro; Kitani, Tomoya; Tabata, Yasuhiko; Matoba, Satoaki; Gojo, Satoshi
Abstract: Acute myocardial infarction is a leading cause of death among single organ diseases. Despite successful reperfusion therapy, ischaemia reperfusion injury (IRI) can induce oxidative stress (OS), cardiomyocyte apoptosis, autophagy and release of inflammatory cytokines, resulting in increased infarct size. In IRI, mitochondrial dysfunction is a key factor, which involves the production of reactive oxygen species, activation of inflammatory signalling cascades or innate immune responses, and apoptosis. Therefore, intercellular mitochondrial transfer could be considered as a promising treatment strategy for ischaemic heart disease. However, low transfer efficiency is a challenge in clinical settings. We previously reported uptake of isolated exogenous mitochondria into cultured cells through co‐incubation, mediated by macropinocytosis. Here, we report the use of transactivator of transcription dextran complexes (TAT‐dextran) to enhance cellular uptake of exogenous mitochondria and improve the protective effect of mitochondrial replenishment in neonatal rat cardiomyocytes (NRCMs) against OS. TAT‐dextran–modified mitochondria (TAT‐Mito) showed a significantly higher level of cellular uptake. Mitochondrial transfer into NRCMs resulted in anti‐apoptotic capability and prevented the suppression of oxidative phosphorylation in mitochondria after OS. Furthermore, TAT‐Mito significantly reduced the apoptotic rates of cardiomyocytes after OS, compared to simple mitochondrial transfer. These results indicate the potential of mitochondrial replenishment therapy in OS‐induced myocardial IRI.